Students' Mathematic Communication Ability in Solving Mathematics Problems from Cognitive Style and Gender - Sigid Edy Purwanto; Wulandari Liga Kusumawati (Budapest International Research and Critics University, 2022)
This study aims to analyze the level of students' mathematical communication skills in solving mathematical problems in terms of cognitive style and gender in the aspects of mathematical writing, drawing, and expression. This is qualitative research with the research subjects are 37 students of VIII class. Sampling was done by purposive sampling technique. Collecting data in this study using written tests and interviews. Data analysis in this study used data collection, reduction, presentation and verification. The results showed that: 1) Students in FD and FI were both able to understand questions and gave good responses, the difference was that FI understood the problem separately while FD understood the problem as a whole; 2) FD can draw based on information on the problem without analyzing the problem but not according to problem solving steps so that there are few errors, while FI are able to draws based on analysis of the information presented correctly and in accordance with problem solving steps but there are unclear for readers; 3) FD and FI can both express results using mathematical equations and present problem solving results based on the results of visualizing the problem, but FI present results are structured while FD are not structured.